Spinors on singular spaces and the topology of causal fermion systems - Finster, Felix, 1967-; Kamran, Niky, 1959- (Memoirs of the American Mathematical Society, 2019)
"Causal fermion systems and Riemannian fermion systems are proposed as aframework for describing non-smooth geometries. In particular, this framework pro-vides a setting for spinors on singular spaces. The underlying topological structuresare introduced and analyzed. The connection to the spin condition in differentialtopology is worked out. The constructions are illustrated by many simple exampleslike the Euclidean plane, the two-dimensional Minkowski space, a conical singularity, a lattice system as well as the curvature singularity of the Schwarzschildspace-time. As further examples, it is shown how complex and K ̈ahler structurescan be encoded in Riemannian fermion systems."--Page v